Every falling star : the true story of how I survived and escaped North Korea - Lee, Sungju; McClelland, Susan (Amulet Books, 2016)
"This is YA nonfiction. It's the memoir of a boy named Sungju who grew up in North Korea and, at the age of twelve, was forced to live on the streets and fend for himself after his parents disappeared. Finally, after years of being homeless and living with a gang, Sungju is reunited with his maternal grandparents and, eventually, his father"--